Case report: Application of nirmatrelvir/ritonavir to treat COVID-19 in a severe aplastic anemia child after allogeneic hematopoietic stem cell transplantation - Huang, Jinhua; Yin, Di; Qin, Xia; Yu, Mei; Jiang, Beilei; Chen, Jing; Cao, Qing; Tang, Zhiguo (Frontiers in Pediatrics, 2022)
We present a case report of successful treatment with nirmatrelvir/ritonavir (Paxlvoid) for a severe aplastic anemia child with COVID-19, cytopenia, and mixed chimerism of donor hematopoietic cells at 3 months after allogeneic hematopoietic stem cell transplantation. After the 5-day entire course of treatment, the clinical symptoms were relieved, cycle threshold values of ORF1a/b and N genes increased from 22.60 and 22.15 to 34.52 and 33.84, respectively, and the peripheral blood counts gradually recovered without graft failure. Nirmatrelvir/ritonavir can effectively inhibit the replication of SARS-CoV-2 without any significant adverse effects.